PENERAPAN PENGARUH METODE PRAKTIKUM TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI SD SWASTA RA KARTINI CERDAS BANGSA - Minta Ito Harahap; Rita Destini; Rahmat Kartolo; Risnawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The objective of the research was to determine the effect of the practicum method on student learning outcomes in Natural and Social Sciences (IPAS) at SD Swasta RA Kartini Cerdas Bangsa in the academic year 2025-2026. This research used a quantitative quasi-experimental design, using two classes: an experimental class taught using the practicum method and a control class taught using the lecture method. Data collection techniques used pretests and posttests to determine improvements in student learning outcomes. The results of this research are as follows: the average pretest score for students before treatment in the experimental class was 54.821 with a standard deviation of 17.239. Meanwhile, in the control class, the average pretest score was 51.852 with a standard deviation of 12.871. Furthermore, student learning outcomes after being given the practicum method in the experimental class obtained an average posttest score of 88.571 with a standard deviation of 12.007. Meanwhile, student learning outcomes after being given the lecture method in the control class obtained an average posttest score of 66.111 with a standard deviation of 5.937. Student learning outcomes were evidenced by the results of the hypothesis test, with a Sig. (2-tailed) value of 0.000 < 0.05 and a t-observed value (8.741) > t-table value (1.6741). Therefore, it can be concluded that Ho is rejected and H1 is accepted. There is an effect of the practicum method on student learning outcomes in science at SD Swasta RA Kartini Cerdas Bangsa